Electrophoresis features and genotypes of Hb bart's hydrops fetalis. (17th February 2020) - Li, Youqiong; Liang, Liang; Tian, Mao; Qing, Ting; Wu, Xin
Abstract: Hydrops fetalis syndrome (Hb Bart's disease) is one of the common fetal development abnormalities and the most severe form of α-thalassemia. It causes fetal death during the third trimester or shortly after birth. The aim of this study is to investigate the feature of Hb Bart's disease by Capillary electrophoresis (CE) and its genotypes. A total of 38 cases of suspected fetal Hb Bart's disease were analyzed by B-ultrasound and CE, including 17 with 24–28 weeks of pregnancy, 9 with 29–32 weeks of pregnancy, and 12 with 33–38 weeks of pregnancy. All cases were then identified by DNA analysis. The minimum concentration of Hb Bart's was 72.2% and the highest 90.9%. Hb Bart's fraction increased while that of Hb Portland decreased with the duration of pregnancy. In order to avoid serious maternal morbidity, it is necessary to diagnose Hb Bart's disease as soon as possible and CE can be used as a method of rapid diagnosis.